Lack of the Golgi phosphate transporter PHT4;6 causes strong developmental defects, constitutively activated disease resistance mechanisms and altered intracellular phosphate compartmentation in Arabidopsis - Haßler, Sebastian; Krüger, Falco; Schumacher, Karin (The plant journal, 2012)
The Golgi-located phosphate exporter PHT4;6 has been described as involved in salt tolerance but further analysis on the physiological impact of PHT4;6 remained elusive. Here we show that PHT4;6-GFP is targeted to the trans-Golgi compartment and that loss of function of this carrier protein has a dramatic impact on plant growth and development. Knockout mutants of pht4;6 exhibit a dwarf phenotype that is complemented by the homologous gene from rice (Oryza sativa). Interestingly, pht4;6 mutants show altered characteristics of several Golgi-related functions, such as an altered abundance of certain N-glycosylated proteins, altered composition of cell-wall hemicelluose, and higher sensitivity to the Golgi α-mannosidase and the retrograde transport inhibitors kifunensine and brefeldin A, respectively. Moreover, pht4;6 mutants exhibit a ‘mimic disease’ phenotype accompanied by constitutively activated pathogen defense mechanisms and increased resistance against the virulent Pseudomonas syringae strain DC3000. Surprisingly, pht4;6 mutants also exhibit phosphate starvation symptoms, as revealed at the morphological and molecular level, although total Pi levels in wild-type and pht4;6 plants are similar. This suggested that subcellular Pi compartmentation was impaired. By use of nuclear magnetic resonance (NMR), increased Pi concentration was detected in acidic compartments of pht4;6 mutants. We propose that impaired Pi efflux from the trans-Golgi lumen results in accumulation of inorganic phosphate in other internal compartments, leading to low cytoplasmic phosphate levels with detrimental effects on plant performance.